X-ray phase-contrast tomosynthesis of a human ex vivo breast slice with an inverse Compton x-ray source - Eggl, E.; Schleede, S.; Bech, Martin; Achterhold, Klaus; Grandl, S.; Sztrokay, A.; Hellerhoff, K.; Mayr, D.; Loewen, R.; Ruth, R. D.; Reiser, M. F.; Pfeiffer, F. (EPL - Europhysics Letters, 2016)
While the performance of conventional x-ray tube sources often suffers from the broad polychromatic spectrum, synchrotrons that could provide highly brilliant x-rays are restricted to large research facilities and impose high investment and maintenance costs. Lately, a new type of compact synchrotron sources has been investigated. These compact light sources (CLS) based on inverse Compton scattering provide quasi-monochromatic hard x-rays. The flux and brilliance yielded by a CLS currently lie between x-ray tube sources and third-generation synchrotrons. The relatively large partially coherent x-ray beam is well suited for the investigation of preclinical applications of grating-based phase-contrast and dark-field imaging. Here we present the first grating-based multimodal tomosynthesis images of a human breast slice acquired at a CLS to investigate the possibilities of improved breast cancer diagnostics.
CRIS-Team Scopus Importer:2023-03-08